The Benthic Megafaunal Assemblages of the CCZ (Eastern Pacific) and an Approach to their Management in the Face of Threatened Anthropogenic Impacts - Tilot, Virginie; Ormond, Rupert; Moreno Navas, Juan; Catalá, Teresa S. (Frontiers in Marine Science, 2018)
We present here the results of a UNESCO/IOC baseline study of the megafaunal assemblages of the polymetallic nodule ecosystem of 5 areas within the Clarion Clipperton Zone (CCZ) of the eastern Pacific Ocean. The work was undertaken with a view to investigating the structure of the epifaunal populations associated with the benthic biotopes being targeted for nodule mining and developing an appropriate set of management tools and options. The general characteristics of nodule ecosystem and assemblages and their sensitivity to deep-sea mining are discussed in relation to water masses, surface to seabed water circulation, the nepheloid layer and processes taking place at the sediment interface. Management tools considered include species diversity and vulnerability indexes, GIS systems, zoning, and 3D rapid environmental assessment (REA). These strategies are proposed for trial during pilot mining operations within the CCZ.